Leveraging Tanzania’s National e-Procurement System for Sustainable Public Procurement: An Empirical Review of Environmental and Operational Outcomes - Yussuf Masoud (African Journal of Empirical Research, 2026)
This research investigated how the National e-Procurement System contributes to sustainable public procurement by analyzing its contribution to sustainable public procurement through four dimensions: reduction of paperwork, carbon emissions reduction, cartridge reduction, and reduction of transportation and communication cost for procuring organizations and suppliers. The study is guided by the natural-resource-based view, transaction cost economics, and the technology-organization-environment framework. An empirical desktop-review design was employed. Data was deliberately selected from Tanzanian laws; Public Procurement Regulatory Authority reports and guidelines; the National e-Procurement System sources; the 2025 Methodology for Assessing Procurement Systems report; and precisely 20 peer-reviewed journal articles published between 2024 and 2026. Thematic analysis was employed to analyze the data. The findings reveal that e-tendering, bidding, evaluation, approval, contract management, and communication minimize the use of paper, copy, bind, and storage processes. Also, the National e-Procurement System saved 617.85 tons of carbon dioxide emissions in one year. Moreover, Tanzania’s National e-Procurement System also eliminates the need for travel on behalf of both the suppliers and the purchasing organization, as well as officers of the purchasing organization. In this way, costs of fuel, fare, accommodation, courier services, and opportunity costs are reduced along with expanding geographical reach for tender documents. The study recommends that Public Procurement Regulatory Authority should integrate a sustainability dashboard into Tanzania’s National e-Procurement System to monitor resource savings and independently verify avoided carbon dioxide emissions. Also, Tanzania’s National e-Procurement System should promote environmentally friendly supplies while the government improves connectivity, training and support to prevent supplier exclusion.